2017
DOI: 10.1002/slct.201700611
|View full text |Cite
|
Sign up to set email alerts
|

Amide Functionalized Ionic Liquid as Facile Fluorescent Probe for Detection of Nitrophenolic Compounds

Abstract: Detection of nitrophenolic compounds has great importance concerning to its environmental and health hazards. Herein, we are exploring a simple, thermally stable amide functionalized task specific ionic liquid (TSIL), 3-(2-amino-2-oxoethyl)-1-methylimidazolium chloride, [AmoMIM] [Cl] as an effective fluorescent probe for detection of water soluble nitrophenolic compounds viz. picric acid (PA) and p-nitrophenol (NP). The proposed method provides a straightforward detection proce-dure anchored in significant qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…The EIS spectroscopy indicates that very lowest depressed semicircle is observed for KOH electrolyte which evidenced for highest specific capacitance. It also indicates that the contact resistance of KOH electrolyte is minimal which possess fast charge transfer [40] . The Nyquist plot also indicated that ZrO 2 nanoparticles derived from imidazole‐based organic precursor have a better tendency towards the supercapacitor application with better conductivity.…”
Section: Resultsmentioning
confidence: 90%
“…The EIS spectroscopy indicates that very lowest depressed semicircle is observed for KOH electrolyte which evidenced for highest specific capacitance. It also indicates that the contact resistance of KOH electrolyte is minimal which possess fast charge transfer [40] . The Nyquist plot also indicated that ZrO 2 nanoparticles derived from imidazole‐based organic precursor have a better tendency towards the supercapacitor application with better conductivity.…”
Section: Resultsmentioning
confidence: 90%
“…In order to further fine‐tune the properties of the ILBSs, recently a new concept of incorporating various functionalities such as hydroxyl, vinyl, ester, amine, ether or amide in the structure of ILBSs has been materialized ,. It is reported that incorporating functionality influences the interfacial and micellar properties significantly.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that incorporating functionality influences the interfacial and micellar properties significantly. For example, ester or amide functionalized ILBSs with imidazolium, pyridinium or morpholinium cations exhibit better surface activity than the homologous traditional cationic surfactants and non‐functionalized ILBSs ,. Recently, we reported the improved interfacial and micellar properties of the vinylfunctionalized ILBSs compared to their saturated analogous ILBS and conventional surfactant .…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon might be attributed to the enhanced charge transfer between SPN-NH 2 and p -NP due to the increased number of quenchers surrounding the probe. 16 To establish the quantitative relationship between the probe's FL intensity and β-gal concentration, the FL variation as a function of β-gal level was recorded. Fig.…”
mentioning
confidence: 99%
“…14,15 The nitro group of p-NP is known as a highly electron-deficient species and hence it could serve as a good electron acceptor in charge transfer systems. 16 In contrast, the amino group-modified SPN-NH 2 can play the role of an electron donor. Thus, we presumed that the FL of SPN-NH 2 might be effectively quenched by p-NP.…”
mentioning
confidence: 99%